Promoting development of entrepreneurial skills of youth in Ghana through a structured sport intervention program - Ocansey, Reginald Tetteh-Ahumah; Nyawornota, Vida Korleki; Adamba, Clement; Tay, Doris Akosua; Musah, Karim; Nyanyofio, Oscar Cornelius Nyanyo; Malete, Leapetswe; McCole, Daniel (Frontiers in Education, 2023)
Introduction The purpose of this brief report is to describe how a structured sport-based positive life skills program can be used in promoting the development of entrepreneurial skills of youth in Ghana. Methods A total of 29 youth participated in the study with 11 as the control group and the remaining 18 as the intervention group. The students in the intervention together with 5 parents participated in a weekend mapping camp. Data for the study was collected with the Youth Experience Survey for Sport to measure the Life skills and entrepreneurship skills using a quasi experimental pre and post test control group design. Results The youth in the intervention group reported important physical and personal benefits and entrepreneurial skills such as cooperation (teamwork), risk taking, creativity, leadership, cognitive development, and positive engagement in physical activity which they did not previously have. The results are similar to existing published papers giving this report a commendable validity and reliability. Discussion Similar to the previously published papers, the perceived gains in this report also show that exposing youth to a structured sport-based positive life skills program produce both physical benefits and development of lifelong skills necessary to develop skills necessary for entrepreneurial endeavors. When this intervention is upscaled in Ghana the country could offset high youth unemployment with its associated challenges.